A novel approach to characterize physical activity patterns in preschool‐aged children. (17th October 2013) - Ruiz, Rachel M.; Tracy, Dustin; Sommer, Evan C.; Barkin, Shari L.
Abstract : Objective: Routine moderate‐to‐vigorous physical activity (MVPA) is associated with better health outcomes; the purpose of this work was to evaluate healthy preschooler physical activity patterns with objective measurement. Methods and Procedures: An objective prospective study of 50 normally developing children 3‐5 years old who were ≥50th and <95th BMI percentile and enrolled in a family‐based healthy lifestyle study in 2011‐2012. Participants wore a tri‐axial accelerometer for 7 continuous days. Outcome measures consisted of wear time examining four common MVPA patterns: isolated spurt (IS), isolated sustained activity (ISA), clustered spurt (CS), and clustered sustained activity (CSA). Results: Participants were 4.3 years, 56% female, 52% African‐American, and 26% overweight. Forty‐five children met wear time criteria. On average, children spent 14.5% of wake‐wear time in MVPA, requiring 11.3 h to complete 90% of their daily MVPA. Children spent the majority of MVPA in CS (62.1%, followed by CSA (20.1%). Remaining MVPA was spent in IS (15.5%) and ISA (2.3%). Conclusion: It takes most of the waking day for preschoolers to attain their PA. They engage in short spurts of small duration, in four common MVPA patterns. Utilizing this method could better characterize preschooler physical activity needs in practice and policy guidelines.